Low Dose of Sucralose Alter Gut Microbiome in Mice - Zheng, Zibin; Xiao, Yingping; Ma, Lingyan; Lyu, Wentao; Peng, Hao; Wang, Xiaorong; Ren, Ying; Li, Jinjun (Frontiers in Nutrition, 2022)
Sucralose is a non-nutritive artificial sweetener (NNS) used in foods or beverages to control blood glucose levels and body weight gain. The consumption of NNS has increased in recent years over the world, many researches have indicated long-term sucralose administration altered the gut microbiome composition of mice. These studies all focus on the US Food and Drug Administration (FDA) defined acceptable daily intake (ADI), approximately 5 mg/kg BW/day for human. In our study, mice were given with T1-4 (0.0003 mg/mL, 0.003 mg/mL, 0.03 mg/mL, 0.3 mg/mL) of sucralose, respectively, Control group mice were given normal water. In particular, 0.3 mg/mL of sucralose was equal to the ADI (5 mg/kg BW/day). After 16 weeks, all mice were weighted and sacrificed, the liver of each mouse was isolated and weighed, segments of jejunum, ileum and colon were collected for H&E-stained. The contents of jejunum, ileum, cecum and colon were collected for 16S rRNA gene sequencing. The results showed sucralose administration affects the intestinal barrier function evidenced by distinct lymphocyte aggregation in ileum and colon while not change the mice body weight. The 16S rRNA gene sequencing of the mice gut microbiome suggested sucralose administration significantly changed the composition of gut microbiota, especially in T1 and T4 group. For example, a reduction of probiotics abundance (Lachnoclostridium and Lachnospiraceae) was found in cecum of T4 group mice compared with Control group. On the other hand, Allobaculum, which was reported positively correlated with diabetes, was increased in the T1 and T4 group. In addition, the potential pathogens, including Tenacibaculum, Ruegeria, Staphylococcus were also increased in jejunum, ileum and colon by sucralose administration in T1 and T4 group. These new findings indicate that low dose of sucralose (T1) alter gut microbiome in mice, and these adverse health effects are equal to ADI level (T4). Overall, our study provides guidance and suggestions for the use of sucralose in foods and beverages.